2012
DOI: 10.1039/c2sm25605c
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of neutral semipermeable shells in asymmetric electrolyte solutions

Abstract: We study the ionic equilibria and interactions of neutral semi-permeable spherical shells immersed in electrolyte solutions, including polyions. Although the shells are uncharged, only one type of ions of the electrolyte can permeate them, thus leading to a steric charge separation in the system. This gives rise to a charge accumulation inside the shell and a build up of concentrationdependent shell potential, which converts into a disjoining pressure between the neighboring shells. These are quantified by usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] In all these systems the uptake, storage, and release of active agents and cosolutes (e.g., reactants, pollutants, ligands, drugs) are decisive processes, which have to be controlled and programmed to the material. The gels in these applications often form film-like layers [11,12], shells, and membranes that modulate the permeation [13,14] and separation of the cosolutes by their wide range of controllable physicochemical behavior. A fundamental property describing the permeation and sorption of cosolutes to polymer networks on the most global level is the partitioning…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In all these systems the uptake, storage, and release of active agents and cosolutes (e.g., reactants, pollutants, ligands, drugs) are decisive processes, which have to be controlled and programmed to the material. The gels in these applications often form film-like layers [11,12], shells, and membranes that modulate the permeation [13,14] and separation of the cosolutes by their wide range of controllable physicochemical behavior. A fundamental property describing the permeation and sorption of cosolutes to polymer networks on the most global level is the partitioning…”
Section: Introductionmentioning
confidence: 99%
“…Based on earlier results, 33 one can expect to observe the same qualitative picture at least at low polyion concentrations, while at the higher concentrations the correlation effects might become significant. 37 We leave the study of the latter regime for a future work.…”
Section: Potentialmentioning
confidence: 99%
“…Recent integral equation study suggested charge correlation effects in large concentration solutions of multivalent ions that could result in short-range attractions. 37 We are unaware of any previous work that has addressed the ques-tion of interaction of a semipermeable membrane with a wall.…”
Section: Introductionmentioning
confidence: 99%
“…The neglect of correlations among ions inherent in the mean-field approximation for Ω is valid for weakly-correlated monovalent ions, but questionable for more strongly correlated multivalent microions. [29][30][31] For this reason, we restrict our considerations to monovalent ions.…”
Section: Poisson-boltzmann Theory Of Bulk Dispersionsmentioning
confidence: 99%
“…25 These ion density differences were attributed to the capsule semipermeability and explained by a macroscopic theoretical model of Donnan equilibrium. 25,27 Vinogradova et al [29][30][31] applied Poisson-Boltzmann (PB) theory to study the osmotic pressure acting on semipermeable shells in polyion solutions. Stukan et al 28 used molecular dynamics simulation to study ion distributions near nanocapsules that are permeable to solvent and counterions, but impermeable to polyelectrolyte coils, which were modeled as soft colloids.…”
Section: Introductionmentioning
confidence: 99%